PENGARUH FAKTOR INTERNAL DAN EKSTERNAL TERHADAP MINAT BERWIRAUSAHA PADA MAHASISWA FAKULTAS EKONOMI UNIVERSITAS ISLAM KALIMANTAN (UNISKA) MUHAMMAD ARSYAD AL-BANJARY BANJARMASIN - Periyadi Periyadi; Junaidi Junaidi (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2019)
Abstract, The research aims to determine whether or not the Influence of Internal and External Factors on Entrepreneurial Interest in Students of the Faculty of Economics, Islamic University of Kalimantan (UNISKA) Muhammad Arsyad Al-Banjary Banjarmasin both partially and simultaneously. The method used in this study is quantitative research, which is a research model that requires the calculation of numbers, while the approach used is a survey approach that is research that takes samples from the population and uses a questionnaire as a basic data collection tool. The results of this research data processing, it turns out that the independent variable that has the largest beta is the external factor variable (X2) that is equal to 0.710. Therefore it can be said that the external factor variable (X2) which has the greatest influence on interest is the variable X2 with a standard regression coefficient of 0.710 or 71%. The results of the first hypothesis (H1) are the decision to reject H0 and accept Ha, which means the F test of the regression equation obtained from this study shows the results that, together the two variables affect the level of interest in entrepreneurship.